Big data analytics of sustainable ecotourism development in Bromo Tengger Semeru National Park - Joshi Maharani Wibowo; Sri Muljaningsih; Dias Satria (Center for Science and Technology, IAIN Surakarta, 2021)
Bromo Tengger Semeru National Park (BTSNP) are designated as the 10 new Bali of Indonesia. As a protected area, BTSNP has unique ecotourism characteristics that distinguish it from other ecotourism destinations. This study seeks to examine the appropriateness of BTSNP sustainable development-based ecotourism through the Sustainable Livelihoods Approach (SLA) approach. This study used TripAdvisor reviews related to BTSNP in 2019 as the main data. The data were analyzed using a qualitative approach. The results of this study revealed the extent to which the process of developing BTSNP ecotourism on the basis of sustainable development as observed from economic, tourism, socio-cultural, and environmental aspects. The results of this study are expected to be considerations for policy-making to develop tourism that pays attention to the environment by not imposing BTSNP boundaries as protected areas for conservation.